2019
DOI: 10.1002/ece3.5575
|View full text |Cite
|
Sign up to set email alerts
|

Protection from illegal fishing and shark recovery restructures mesopredatory fish communities on a coral reef

Abstract: The recovery of communities of predatory fishes within a no‐take marine reserve after the eradication of illegal fishing provides an opportunity to examine the role of sharks and other large‐bodied mesopredatory fishes in structuring reef fish communities. We used baited remote underwater video stations to investigate whether an increase in sharks was associated with a change in structure of the mesopredatory fish community at Ashmore Reef, Western Australia. We found an almost fourfold increase in shark abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 84 publications
4
16
0
Order By: Relevance
“…These findings further highlight the efficiency of using BRUVS to survey and monitor elasmobranch species at remote and isolated islands from the ETP, some of which are recognized as UNESCO World Heritage sites. www.nature.com/scientificreports/ Numerous studies have demonstrated that shark abundances are generally greater inside than outside not-take MPAs 19,22,54 , which is in agreement with our findings. However, BRUVS deployed at Caño and Murciélago islands had significantly less species and lower abundances compared to Cocos Island.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings further highlight the efficiency of using BRUVS to survey and monitor elasmobranch species at remote and isolated islands from the ETP, some of which are recognized as UNESCO World Heritage sites. www.nature.com/scientificreports/ Numerous studies have demonstrated that shark abundances are generally greater inside than outside not-take MPAs 19,22,54 , which is in agreement with our findings. However, BRUVS deployed at Caño and Murciélago islands had significantly less species and lower abundances compared to Cocos Island.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, BRUVS provide a relatively cost-effective survey method that enhances predator detection by using bait and overcomes fish avoidance issues with divers 25,49,50 . Moreover, permanent footage generated through BRUVS can be used to answer specific behavioral questions 51 or shared with other researchers to support regional and global conservation efforts such as the one lead by the Global FinPrint Project 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong attractiveness of bait to sharks [9], has also made BRUVs efficient tools for assessing shark populations. For example, a recent worldwide project (see www.globalfinprint.com) [10] deployed thousands of BRUVs across the globe, and allowed drivers-such as heavy fishing pressure or illegal fishing-for diversities and densities of coastal sharks, to be identified [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The gray reef shark, Carcharhinus amblyrhynchos (Carcharhinidae), has a broad tropical distribution ranging from the Western Indian to the Central Pacific Oceans. This large-bodied shark is commonly associated with coral reefs where it can constitute a major proportion of the high trophic-level predator biomass, and likely plays an important role in structuring reef communities (Friedlander et al 2014;Speed et al 2019). Stemming recent declines in reef shark species caused by overfishing requires urgent management and conservation measures, with concomitant information on the genetic dynamics of reef shark populations to guide these efforts (Heupel et al 2019).…”
mentioning
confidence: 99%